Correction for Delay and Dispersion Results in More Accurate Cerebral Blood Flow Ischemic Core Measurement in Acute Stroke. Issue 4 (April 2018) - Lin, Longting; Bivard, Andrew; Kleinig, Timothy; Spratt, Neil J.; Levi, Christopher R.; Yang, Qing; Parsons, Mark W.
Abstract : Background and Purpose—: This study aimed to assess how the ischemic core measured by perfusion computed tomography (CTP) was affected by the delay and dispersion effect. Methods—: Ischemic stroke patients having CTP performed within 6 hours of onset were included. The CTP data were processed twice, generating standard cerebral blood flow (sCBF) and delay- and dispersion-corrected CBF (ddCBF), respectively. Ischemic core measured by the sCBF and ddCBF was then compared at the relative threshold <30% of normal tissue. Two references for ischemic core were used: acute diffusion-weighted imaging or 24-hour diffusion-weighted imaging in patients with complete recanalization. Difference of core volume between CTP and diffusion-weighted imaging was estimated by Mann–Whitney U test and limits of agreement. Patients were also classified into favorable and unfavorable CTP patterns. The imaging pattern classification by sCBF and ddCBF was compared by the χ 2 test; their respective ability to predict good clinical outcome (3-month modified Rankin Scale score) was tested in logistic regression. Results—: Fifty-five patients were included in this study. Median sCBF ischemic core volume was 38.5 mL (12.4–61.9 mL), much larger than the median core volume of 17.2 mL measured by ddCBF (interquartile range, 5.5–38.8; P <0.001). Moreover, compared with sCBF <30%, ddCBF <30% measured the ischemic core much closer to diffusion-weighted imaging core references, with the mean volume difference of −0.1 mL (95% limits of agreement, −25.4 to 25.2; P =0.97) and 16.7 mL (95% limits of agreement, −21.7 to 55.2; P <0.001), respectively. Imaging patterns defined by sCBF showed a difference to that defined by ddCBF ( P <0.001), with 12 patients classified as favorable imaging patterns by ddCBF but as unfavorable by sCBF. The favorable imaging pattern classified by ddCBF, compared with sCBF classification, had higher predictive power for good clinical outcome (odds ratio, 7.8 [2–30.5] and 3.1 [0.9–11], respectively). Conclusions—: Delay and dispersion correction increases the accuracy of ischemic core measurement on CTP. Abstract : Supplemental Digital Content is available in the text.